2006
DOI: 10.3989/cyv.2006.v45.i2.321
|View full text |Cite
|
Sign up to set email alerts
|

Estudio de la Citotoxicidad de Cerámicas Biomórficas de SiC Recubiertas con Vidrio Bioactivo

Abstract: La necesidad de desarrollar nuevos implantes basados en materiales bioactivos que sean capaces de soportar grandes cargas mecánicas ha llevado a la producción de sustratos metálicos recubiertos con cerámicas bioactivas. Recientemente se ha propuesto un dispositivo alternativo que consiste en un sustrato de carburo de silicio (SiC) biomórfico recubierto con vidrio bioactivo, mediante la técnica de Depósito por Láser Pulsado (PLD), y que dispone de la resistencia mecánica adecuada, además de gran ligereza y una … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…The obtained biomorphic SiC is characterized by porosity and mechanical features similar to that of bone tissue. They tested different types of wood and BG with different compositions [159][160][161], obtaining promising results for the application of these systems in hard-tissue related implants. Another revolutionary route for improving implants osteointegration is the production of bioresorbable implants, generally made in Mg and its alloys, which are supposed to be completely degraded after the bone healing [162].…”
Section: Pld Of Glass and Glass-ceramic Coatingsmentioning
confidence: 99%
“…The obtained biomorphic SiC is characterized by porosity and mechanical features similar to that of bone tissue. They tested different types of wood and BG with different compositions [159][160][161], obtaining promising results for the application of these systems in hard-tissue related implants. Another revolutionary route for improving implants osteointegration is the production of bioresorbable implants, generally made in Mg and its alloys, which are supposed to be completely degraded after the bone healing [162].…”
Section: Pld Of Glass and Glass-ceramic Coatingsmentioning
confidence: 99%
“…In the first phase, the evaporation of absorbed water occurs at 150 • C. In the second phase, this water loss leads to the breaking of the structure of cellulose between 150 and 240 • C. The third phase is the decomposition of organic polymers, mainly hemicellulose, due to the breaking of C-C and C-O bonds between 240 and 400 • C, resulting in the release of carbon monoxide, carbon dioxide and water. Finally, the decomposition of cellulose and lignin begins at 290 • C at a high rate until 400 • C and more slowly up to the final 500 • C. Therefore, the restructuring of the carbon atoms, the release of residual hydrogen and elimination of defects cause an increase in the degree of crystallinity begins at temperatures higher than 400 • C (Borrajo 2006, Byrne and Nagle 1997, Tang and Bacon 1964. Moreover, Pappacena et al (2009) have demonstrated, after subjecting wood to a 1 hpyrolysis process at temperatures between 400 and 2500 • C, that the obtained carbon is always turbostratic and not graphite.…”
Section: Carbonmentioning
confidence: 99%